Augmenting Antitumor Immune Responses with Epigenetic Modifying Agents - Héninger, Erika; Krueger, Timothy E. G.; Lang, Joshua M. (Frontiers in Immunology, 2015)
Epigenetic silencing of immune-related genes is a striking feature of the cancer genome that occurs in the process of tumorigenesis. This phenomena impacts antigen processing and antigen presentation by tumor cells and facilitates evasion of immunosurveillance. Further modulation of the tumor microenvironment by altered expression of immunosuppressive cytokines impairs antigen presenting cells and cytolytic T cell function. The potential reversal of immunosuppression by epigenetic modulation is therefore a promising and versatile therapeutic approach to reinstate endogenous immune recognition and tumor lysis. Preclinical studies have identified multiple elements of the immune system that can be modulated by epigenetic mechanisms and result in improved antigen presentation, effector T cell function, and breakdown of suppressor mechanisms. Recent clinical studies are utilizing epigenetic therapies prior to, or in combination with, immune therapies to improve clinical outcomes. This review will summarize pre-clinical and clinical studies evaluating the combination of epigenetic modifying agents with anti-tumor immunotherapies.